Short-course intravenous beta-lactams for uncomplicated cystitis in hospitalized patients - Payton Simpson; Katie Wallace; Katherine Olney; Danielle Casaus; David S. Burgess; Aric Schadler; Abigail Leonhard; Jeremy VanHoose (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract